2018
DOI: 10.3233/jpd-181305
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Undiagnosed Insulin Resistance in Non-Diabetic Subjects with Parkinson’s Disease

Abstract: IR is prevalent in PD and it correlates with BMI. A correlation between IR with cognitive and QoL measures cannot be determined on the basis of this sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 47 publications
1
39
0
Order By: Relevance
“…Insulin signaling impairment and insulin resistance have been observed in neurodegenerative diseases such as AD (Talbot et al, 2012) and PD (Hogg et al, 2018) (Figure 2). Diabetes mellitus, FIGURE 2 | The connection between insulin signaling and neurodegenerative disease.…”
Section: Insulin In Neurodegenerative Diseasementioning
confidence: 99%
“…Insulin signaling impairment and insulin resistance have been observed in neurodegenerative diseases such as AD (Talbot et al, 2012) and PD (Hogg et al, 2018) (Figure 2). Diabetes mellitus, FIGURE 2 | The connection between insulin signaling and neurodegenerative disease.…”
Section: Insulin In Neurodegenerative Diseasementioning
confidence: 99%
“…The PD network module associated with insulin resistance is not preserved in HCs. Insulin resistance is increasingly being shown to be important in PD as a potential therapeutic target [29] and has a high prevalence in non-diabetic PD patients [30], additionally insulin receptor signaling pathways are disturbed in PD [11]. Within this module we identified HDAC6 as a hub gene which promotes the formation of inclusions from α-synuclein toxic oligomers [31].…”
Section: Discussionmentioning
confidence: 99%
“…Among the seven phenotypes in this subcluster, several were known to be correlated based on previous epidemiological studies. For example, in addition to the connection between fasting insulin and breast cancer discussed above, insulin was linked to several phenotypes in this cluster: 1) there is a high prevalence of insulin resistance in non-diabetic Parkinson's disease patients [67] ; 2) it was suggested that abnormal insulin signaling underlies increased autism risk based on the evidence that mutations that hyperactivate PI3K pathway cause autism [68]; 3) insulin resistance co-occurs with hypertension [69]; 4) insulin may work to stimulate osteoblast differentiation, and diabetes have a higher risk of bone fracture [70]. These evidences suggest that insulin signaling may be one of the physiological processes that connect these phenotypes together.…”
Section: Two Way Bi-clustering Detects Subsets Of Genes Co-associatedmentioning
confidence: 93%